Isophasic parasitism in Phoradendron perredactum (Viscaceae) - Kuijt, Job (Instituto de Ecología, A.C., 2011)
It is pointed out that the newly described Phoradendron perredactum Rzedowski & Calderón exhibits an advanced type of growth behavior (isophasic parasitism) that also occurs in three other, unrelated groups of parasitic flowering plants.